Straregi Pemerintah Desa Dalam Pengembangan Pariwisata Sebagai Desa Wisata Alam Di Desa Leppangeng Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - St. Soeraya; Barisan; Jabbar, Abdul (UIR PRESS, 2020)
This study aims to analyze the strategy of the village government in developing Leppangeng Village as a natural tourism village in Pitu Riase District, Sidenreng Rappang Regency.This research use desciptive qualitative approach. The results showed that the village government strategy in developing tourism was using the Development Strategy. The implementation is carried out by increasing the status of tourism, coordinating with people related to stakeholders and tourism-related agencies. In addition, the village government also develops capacity and resources, by conducting training, socialization, and forming tourism awareness groups to improve the capacity of the Leppangeng Village community.